Cross Talk Between Zinc-Solubilizing Bacteria and Plants: A Short Tale of Bacterial-Assisted Zinc Biofortification - Upadhayay, Viabhav Kumar; Singh, Ajay Veer; Khan, Amir (Frontiers in Soil Science, 2022)
A contemporary approach to bacterially mediated zinc biofortification offers a new dimension in crop improvement program with better zinc (Zn) uptake in plants to curb Zn malnutrition. The ZSB (Zn solubilizing bacteria) implication represents an inexpensive and optional strategy for Zn biofortification, with an ultimate greener solution to enlivening sustainable agriculture. ZSB dwelling in the rhizospheric hub or internal plant tissues show competence to solubilize Zn via a variety of strategies. The admirable method is the deposition of organic acids (OAs), which acidify the surrounding soil environment. The secretion of siderophore as a metal chelating molecule, chelating ligands and the manifestation of an oxidative-reductive system on the bacterial cell membrane are further tactics of bacterially mediated zinc solubilization. Inoculation of plants with ZSB is probably a more effective tactic for enhanced zinc translocation in various comestible plant parts. ZSB with plant growth-enhancing properties can be used as bioelicitors for sustainable plant growth via various approaches that are crucial for plant health and its productivity. The present manuscript provides an overview of the functional properties of the ZSB-mediated Zn localization in edible sections of food crops and provides an impetus to explore such plant probiotics as natural biofortification agents.